Speech and language intervention for boys with fragile X syndrome. Case study - Wiech, Tomasz (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
The article concerns the problem of communication and speech disorders for fragile X syndrome. Additionally, disorders which have an impact on the therapeutic process were characterized. The article presents differences in disorders depending on a gender. The article also presents the case study of a 4-year-old boy with FRA X.